A Bayesian Reanalysis of a Trial of Psilocybin versus Escitalopram for Depression - Nayak,SM; Bari,BA; Yaden,DB; Spriggs,MJ; Rosas,F; Peill,JM; Giribaldi,B; Erritzoe,D; Nutt,D; Carhart-Harris,R (2022)
Objectives: To perform a Bayesian reanalysis of a recent trial of psilocybin (COMP360) versus escitalopram for Major Depressive Disorder (MDD) in order to provide a more informative interpretation of the indeterminate outcome of a previous frequentist analysis.Design: Reanalysis of a two-arm double-blind placebo controlled trial.Participants: Fifty-nine patients with MDD.Interventions: Two doses of psilocybin 25mg and daily oral placebo versus daily escitalopram and 2 doses of psilocybin 1mg, with psychological support for both groups.Outcome measures: Quick Inventory of Depressive Symptomatology–Self-Report (QIDS SR-16), and three other depression scales as secondary outcomes: HAMD-17, MADRS, and BDI-1A.Results: Using Bayes factors and ‘skeptical priors’ which bias estimates towards zero, for the hypothesis that psilocybin is superior by any margin, we found indeterminate evidence for QIDS SR-16, strong evidence for BDI-1A and MADRS, and extremely strong evidence for HAMD-17. For the stronger hypothesis that psilocybin is superior by a ‘clinically meaningful amount’ (using literature defined values of the minimally clinically important difference), we found moderate evidence against it for QIDS SR-16, indeterminate evidence for BDI-1A and MADRS, and moderate evidence supporting it for HAMD-17. Furthermore, across the board we found extremely strong evidence for psilocybin’s non-inferiority versus escitalopram. These findings were robust to prior sensitivity analysis.Conclusions: This Bayesian reanalysis supports the following inferences: 1) that psilocybin did indeed outperform escitalopram in this trial, but not to an extent that was clinically meaningful—-and 2) that psilocybin is almost certainly non-inferior to escitalopram. The present results provide a more precise and nuanced interpretation to previously reported results from this trial, and support the need for further research into the relative efficacy of